2007
DOI: 10.1177/0192513x06296117
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Variations in Parental Health Beliefs, Knowledge, and Information Sources Related to Attention-Deficit/Hyperactivity Disorder

Abstract: This study explores cultural variance in parental health beliefs, knowledge, and information sources related to attention-deficit/hyperactivity disorder (ADHD). Structured interviews were completed by a representative community sample of 1,615 parents, including an ADHD knowledge and perceptions survey, behavioral questionnaires, and inquiries about ADHD detection and treatment. Most parents had heard about ADHD and considered themselves knowledgeable about it but were unaware of relevant school services; thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 51 publications
1
39
0
2
Order By: Relevance
“…Bussing and colleagues examined parental etiological beliefs for ADHD in different ethnic groups (Bussing et al, 1998a;Bussing Gary, Mills, & Garvan, 2008;Bussing, Schoenberg, Rogers, Zima & Angus, 1998b). Results indicated that African American parents were more likely to label inattentive and hyperactive/impulsive behavior as "problem" behavior, to consider their child "bad," and to believe that sugar had a role in their child's behavior, whereas White parents were more likely to use a medical label to describe their child's behavior (Bussing et al, 1998a;Bussing et al, 1998b).…”
Section: Perceptions Of the Etiology Of Adhdmentioning
confidence: 99%
See 2 more Smart Citations
“…Bussing and colleagues examined parental etiological beliefs for ADHD in different ethnic groups (Bussing et al, 1998a;Bussing Gary, Mills, & Garvan, 2008;Bussing, Schoenberg, Rogers, Zima & Angus, 1998b). Results indicated that African American parents were more likely to label inattentive and hyperactive/impulsive behavior as "problem" behavior, to consider their child "bad," and to believe that sugar had a role in their child's behavior, whereas White parents were more likely to use a medical label to describe their child's behavior (Bussing et al, 1998a;Bussing et al, 1998b).…”
Section: Perceptions Of the Etiology Of Adhdmentioning
confidence: 99%
“…Results indicated that African American parents were more likely to label inattentive and hyperactive/impulsive behavior as "problem" behavior, to consider their child "bad," and to believe that sugar had a role in their child's behavior, whereas White parents were more likely to use a medical label to describe their child's behavior (Bussing et al, 1998a;Bussing et al, 1998b). Additionally, they found that African American parents were less likely to have heard of ADHD, and few parents were aware of special services available to children with ADHD (Bussing et al, 2008).…”
Section: Perceptions Of the Etiology Of Adhdmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies support a link between socioeconomic status and parental reports of child ADHD symptoms and treatment outcomes (e.g., Larson et al 2011;Rieppi et al 2002). Socioeconomic level may impact a variety of factors related to parents' identification of child ADHD symptoms, including knowledge of ADHD (Bussing et al 2007) or access to mental health information and treatments (Larson et al 2011). Other studies consistently relate maternal depressive symptoms to inaccuracies or biases in reports of child ADHD symptoms (Chi and Hinshaw 2002;Johnston and Short 1993).…”
mentioning
confidence: 98%
“…(Walker, 2004;Wilson, Dalberth, Koo & Gard, 2010;Stone, Ingham & Gibbins, 2013). However, only a few studies exist regarding the http: //dx.doi.org/10.15405/epsbs.2016.12.61 eISSN: 2357-1330 responsibility of the Organizing Committee of the conference 498 use of social media and of asynchronous discussions boards (or discussion forums) by parents seeking information regarding their children's health in general or on specific topics (e.g., pregnancy, early parenting, childhood obesity, mental health, congenital heart diseases and other chronic health conditions) (Appleton, Fowler & Brown, 2014;Bussing, Gary, Mills & Garvan, 2007;Goldman & Macpherson, 2006;Bouche & Migeot, 2008).…”
Section: Introductionmentioning
confidence: 99%